Intra-lineage microevolution of Wolbachia leads to the emergence of new cytoplasmic incompatibility patterns. - Alice Namias; Annais Ngaku; Patrick Makoundou; Sandra Unal; Mathieu Sicard; Mylène Weill (PLoS Biology, 2024)
Mosquitoes of the Culex pipiens complex are worldwide vectors of arbovirus, filarial nematodes, and avian malaria agents. In these hosts, the endosymbiotic bacteria Wolbachia induce cytoplasmic incompatibility (CI), i.e., reduced embryo viability in so-called incompatible crosses. Wolbachia infecting Culex pipiens (wPip) cause CI patterns of unparalleled complexity, associated with the amplification and diversification of cidA and cidB genes, with up to 6 different gene copies described in a single wPip genome. In wPip, CI is thought to function as a toxin-antidote (TA) system where compatibility relies on having the right antidotes (CidA) in the female to bind and neutralize the male's toxins (CidB). By repeating crosses between Culex isofemale lines over a 17 years period, we documented the emergence of a new compatibility type in real time and linked it to a change in cid genes genotype. We showed that loss of specific cidA gene copies in some wPip genomes results in a loss of compatibility. More precisely, we found that this lost antidote had an original sequence at its binding interface, corresponding to the original sequence at the toxin's binding interface. We showed that these original cid variants are recombinant, supporting a role for recombination rather than point mutations in rapid CI evolution. These results strongly support the TA model in natura, adding to all previous data acquired with transgenes expression.